Recording Electrical Brain Activity with Novel Stretchable Electrodes Based on Supersonic Cluster Beam Implantation Nanotechnology on Conformable Polymers - Gnatkovsky V (Dove Medical Press, 2019)
Vadym Gnatkovsky,1 Alessandro Cattalini,1 Alessandro Antonini,2 Laura Spreafico,2 Matteo Saini,2 Francesco Noè,1 Camilla Alessi,1 Laura Librizzi,1 Laura Uva,1 Carlo Efisio Marras,3 Marco de Curtis,1 Sandro Ferrari2 1Unit of Epileptology, Fondazione IRCCS Istituto Neurologico Carlo Besta, Milano, Italy; 2WISE Srl, Cologno Monzese, Milano, Italy; 3Neurosurgery Unit, Department of Neuroscience and Neurorehabilitation, IRCCS Bambino Gesù Children’s Hospital, Roma, ItalyCorrespondence: Vadym GnatkovskyUnit of Epileptology, Fondazione IRCCS Istituto Neurologico Carlo Besta, Via Amadeo, 42, Milano 20133, ItalyTel +39 0223944518Email Vadym.Gnatkovsky@istituto-besta.itBackground: Multielectrodes are implanted in central and peripheral nervous systems for rehabilitation and diagnostic purposes. The physical resistance of intracranial devices to mechanical stress is critical and fractures or electrode displacement may occur. We describe here a new recording device with stretchable properties based on Supersonic Cluster Beam Implantation (SCBI) technology with high mechanical adaptability to displacement and movement.Results: The capability of SCBI-based multichannel electrodes to record brain electrical activity was compared to glass/silicon microelectrodes in acute in vitro experiments on the isolated guinea pig brain preparation. Field potentials and power frequency analysis demonstrated equal recording features for SCBI and standard electrodes. Chronic in vivo epidural implantation of the SCBI electrodes confirmed excellent long-term recording properties in comparison to standard EEG metal electrodes. Tissue biocompatibility was demonstrated by neuropathological evaluation of the brain tissue 2 months after the implantation of the devices in the subarachnoid space.Conclusion: We confirm the biocompatibility of novel SCBI-based stretchable electrode devices and demonstrate their suitability for recording electrical brain activity in pre-clinical settings.Keywords: brain, field potentials, recording electrodes, supersonic cluster beam implantation